2014
DOI: 10.1016/j.jvs.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular-first approach is not associated with worse amputation-free survival in appropriately selected patients with critical limb ischemia

Abstract: At 5 years, endo-first and open-first revascularization strategies had equivalent LS rates and AFS in patients with critical limb ischemia when properly selected. A patient-centered approach with close surveillance improves long-term outcomes for both open and endo approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…The trial also noted that in the context of femoropopliteal bypass, primary conventional bypass surgery was appropriate for patients with a life expectancy of > 2 years and acceptable autogenous conduits [1]. Despite these considerations of the large randomised BASIL trial, two recently reported studies showed that amputation-free survival was not adversely infl uenced by unsuccessful prior angioplasty [17,18]. These observations are in accordance with our results.…”
Section: Discussionsupporting
confidence: 90%
“…The trial also noted that in the context of femoropopliteal bypass, primary conventional bypass surgery was appropriate for patients with a life expectancy of > 2 years and acceptable autogenous conduits [1]. Despite these considerations of the large randomised BASIL trial, two recently reported studies showed that amputation-free survival was not adversely infl uenced by unsuccessful prior angioplasty [17,18]. These observations are in accordance with our results.…”
Section: Discussionsupporting
confidence: 90%
“…4 Nevertheless, there are still concerns that endovascular failure may complicate subsequent open procedures or even preclude a previously feasible OBP opportunity, leaving the patient with only amputation as an option. [5][6][7] Our objective was to evaluate the anatomic changes and long-term clinical outcomes of patients who underwent a lower extremity OBP operation after failure of femoropopliteal endovascular treatment (EVT) for lifestyle-limiting claudication and critical limb ischemia (CLI).…”
mentioning
confidence: 99%
“…[1][2][3][4] Since the BASIL study (Bypass versus Angioplasty in Severe Ischemia of the Leg), 5 it has been proposed that the therapeutic method should be selected based on life expectancy and the presence of a durable vein for CLI patients who were eligible for bypass surgery (BSG) or EVT. 6,7 However, the characteristics of patients who receive BSG seem to differ greatly from patients who undergo EVT in clinical practice, 8 and only a few patients are eligible for either revascularization method. In addition, the efficacy of self-expanding nitinol stents for femoropopliteal lesions has improved 9,10 ; however, infrapopliteal intervention is needed in quite a few cases.…”
mentioning
confidence: 99%